Strategi Persiapan Akreditasi Lembaga Pelatihan Kesehatan: Analisis Mixed-Methods pada DCG Indonesia - Birowo, Anandito; Hidayat, Dasrun; Mulyani, Kahar (Jurnal Pengabdian Nasional (JPN) Indonesia, 2025)
Health training institution accreditation in Indonesia by the Directorate of Health Worker Quality Improvement faces substantial challenges, with over 58% of training institutions lacking accredited status in 2024. DCG Indonesia exemplifies institutions experiencing participant decline due to non-accredited status. The study aims to describe the accreditation preparation process implemented by DCG Indonesia and evaluate the effectiveness of community service activities through accreditation preparation webinars. The research employs a sequential exploratory mixed-methods approach across two phases. The first phase collects qualitative data through in-depth interviews and observations involving five participants directly engaged in the accreditation process, while the second phase utilizes quantitative data from surveys administered to 30 respondents. Research findings demonstrate that DCG Indonesia executed accreditation preparation through document analysis, accreditation team formation, and digital technology implementation. The webinar conducted as post-accreditation community service activities successfully enhanced participant understanding by 75.59% with satisfaction levels reaching 92.7%. The study concludes that systematic accreditation preparation strategies and digital technology adoption can facilitate health training institution accreditation processes. Webinar activities proved effective in improving participant understanding and satisfaction while providing guidance for other non-accredited institutions in accreditation preparation.